Changes in tourist decisions in the shadow of the global crisis – how travel preferences and consumer priorities evolved during COVID-19 and beyond - Behringer, Zsuzsanna; Kulcsár, Noémi; Hinek, Mátyás; Tevely, Titanilla (Marketing & Menedzsment, 2023)
THE AIM OF THE PAPER The aim of the research is to gain a comprehensive picture of the changes in the travel habits of Hungarians in the post-pandemic period. The study sought to answer how the supply side should respond to the economic crisis and what new trends and patterns can be detected in consumer behavior, especially in terms of destination choice, motivations, and sustainability. METHODOLOGY A questionnaire-based survey was conducted online. The sampling method was a convenience sample, aiming to select respondents from the widest possible range of the Hungarian population. Among the 672 respondents, all age groups were represented, while the proportion of respondents who live in Budapest and have secondary or higher education was relatively high. In addition to statistical indicators, the analysis revealed multivariate correlations, showing characteristic features of consumer behavior in each age group segment. MOST IMPORTANT RESULTS Hungarians drastically reduced their leisure travel in 2020 due to forced closures, travel restrictions, and fears (Behringer et al. 2022). This cautious behavior and new trends (e.g. preference for domestic travel, traveling less frequently) remained even in 2021. The new motivations, such as “escape from quarantine”, mental recharging, and interest in outdoor activities also persisted, but health security lost its importance. As economic difficulties increased, the focus shifted to considerations of savings and individual financial circumstances. RECOMMENDATIONS The pandemic has created a new era in the travel market, for both consumers and service providers. The new trends require strong adaptability, flexibility, and responsiveness on the supply side from individual service providers. Supply side operators will have to adapt to new consumer needs if they want to meet tourists’ expectations and retain customers.